Trajnostni prostorski razvoj v visokošolskem izobraževanju - Terlević, Maja (Urbani izziv, 2015)
Sustainable development is not only a great challenge for society as a whole, but also for higher education institutions, which have been rapidly including sustainable development in their educational process in the last two decades. Directly or indirectly, education for sustainable spatial development includesall aspects of sustainable development: environmental, economic, social and cultural. Space is a junction of various interests, which requires coordinating the entire process of spatial planning, taking into account the goal of sustainable spatial development. The existing values of space are insufficient for the rapid implementation of a sustainable spatial developmentparadigm. Suitable education is needed by both individuals and spatial planning professionals and at all levels of education. It is thereforenecessary to transform some of the academic programs in the higher education curriculum by integrating teaching content and methods that include long-term knowledge and holistic thinking, taking into account the importance of interdisciplinary integration. This article reviews literature in sustainable development in higher education from 2002 to 2013. Topics discussed include students' and teachers' conceptions of sustainable development, the presence of sustainable development and sustainable spatial development in higher education and the reasons for the slow introduction of this material into the curriculum. Based on a literature analysis, the last section identifies important drivers that can contribute to a more rapid integration of a sustainable spatial development paradigm into higher education.
Keywords: curriculum; kurikulum; prostorski razvoj; sustainable development; trajnostni razvoj; učni predmeti; visoko šolstvo